Peran Layanan Konseling Individu dalam Mengurangi Isolasi Sosial dan Meningkatkan Relasi Sebaya Siswa di SMA - Mariana Astuti; Latif Hamidi; Baiq Mahyatun; Indah Sofianita; Yuliana Eka Safitri; Silmi Rostiana; Rizkia Maulida; Sridewi Supriyani; Muzayyin Fanani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Social isolation and peer rejection potentially impede students' psychological development and academic achievements. This qualitative descriptive case study aims to analyze students' social isolation profiles to formulate a comprehensive, sociometry-based individual counseling intervention framework at SMAN 3 Selong. Data were collected from 35 participants in class 10-1 through a multiple-criteria sociometric questionnaire encompassing personal, social, learning, and career domains complemented by in-depth interviews and document review. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The sociometric findings indicated a sharp social polarization within the classroom, where eight students were classified as low status and two students experienced total social isolation (zero choices) due to group exclusion (cliques). Sociogram visualizations confirmed unilateral interaction preferences lacking reciprocity across all four orientation domains. Based on these empirical data, an individual counseling intervention was formulated, comprising three systematic clinical stages: core exploration of rejection issues, cognitive restructuring, and social skills training. This personal intervention framework is recommended as an applicable guide for school counselors to mitigate social isolation and optimize students' interpersonal cohesion.